2017
DOI: 10.1123/jpah.2016-0366
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Breaking Up Seated Office Work With Standing or Light-Intensity Walking on Interstitial Glucose Concentration: A Randomized Crossover Trial

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms Results: Five-hour interstitial glucose incremental area under the curve (iAUC) was 55.5% lower after sitting interrupted by light-intensity walking compared with after uninterrupted sitting (95% CI, -104.2% to -6.8%). There was also a suggestion of a beneficial effect of regular stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(42 citation statements)
references
References 24 publications
0
42
0
Order By: Relevance
“…It is important to note that these studies generally induce short interruptions to otherwise long periods of sitting, which differs from the more sustained nonambulatory postures used by the Hadza. Nonetheless, metaanalyses of these experimental studies suggest interrupting sitting with MVPA and with lighter intensity activities seems to improve biomarkers associated with CVD and metabolic disease (37)(38)(39). Studies of interrupted sitting with periods of standing have generated more mixed results (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is important to note that these studies generally induce short interruptions to otherwise long periods of sitting, which differs from the more sustained nonambulatory postures used by the Hadza. Nonetheless, metaanalyses of these experimental studies suggest interrupting sitting with MVPA and with lighter intensity activities seems to improve biomarkers associated with CVD and metabolic disease (37)(38)(39). Studies of interrupted sitting with periods of standing have generated more mixed results (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, metaanalyses of these experimental studies suggest interrupting sitting with MVPA and with lighter intensity activities seems to improve biomarkers associated with CVD and metabolic disease (37)(38)(39). Studies of interrupted sitting with periods of standing have generated more mixed results (37)(38)(39). Although results of these studies underscore the importance of MVPA for cardiometabolic health, some interventions hint at the idea that interrupting sitting with lower activity intensities can produce differential effects on physiological markers associated with cardiometabolic disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…People who were overweight [71] or had lower CRF [81] experienced greater attenuation in post-prandial glucose. Subgroup analysis showed that those who were physically inactive, or had IFG or type 2 diabetes, experienced statistically significant greater glycaemic benefits from PA breaks, and attenuation of insulin also approached significance (Figs.…”
Section: Other Biasmentioning
confidence: 99%
“…Furthermore, blood was drawn, for example, just before PA breaks [46,47] or in rested, sedentary conditions, 1 day after PA breaks [7,8], every 10 min [16], once every 2 h [10,20] or assessed via CGMS [12,14,15,22,71,82,83]. Thus, results could have been affected by differing blood draw protocols [99,147].…”
Section: Other Biasmentioning
confidence: 99%
“…In 20 trials, interventions occurred in a laboratory or research facility where participants were supervised during each condition [12, 14, 16, 18, 20, 30, 32–50]. One trial was completed under supervised conditions in an office setting [51] and nine trials were conducted in a laboratory or research facility [19, 31, 52–58] where participants where not reported to be observed during conditions.…”
Section: Resultsmentioning
confidence: 99%